Hydrogen Sulfide Promotes Functional Endometrium Recovery via Regulating Pyroptosis in Severe Endometrial Injury: A Prospective Laboratory Based Randomized Control Trial - Haiyan Shan; Mingyuan Xu; Jie Ni; Ling Zhou; Mengchun Xue; Jun Xue; Xiaohuan Yuan; Luyang Tao; Mingyang Zhang; Hong Zhang (Clinical and Experimental Obstetrics & Gynecology)
Background: Severe endometrial injury constitutes a significant risk to female fertility, often leading to the development of intrauterine adhesions. Pyroptosis, a form of programmed cell death associated with inflammation, is initiated by the cleavage of gasdermin family proteins by caspase, which has been implicated in endometrial injury. In recent years, hydrogen sulfide (H2S), a gaseous signaling molecule, exerts significant regulatory effects on pyroptosis in diverse pathological processes. The aim of this study is to elucidate the role of H2S in facilitating functional recovery of the endometrium following injury in a murine model. Methods: A prospective laboratory based randomized control trial was performed to evaluate the protective role of H2S in endometrial injury. Ethanol-induced endometrial injury mouse models were established and H2S donor sodium hydrosulfide (NaHS) was randomly administered to the injured mice. Western blot analysis was conducted to assess changes in the expression of endogenous H2S metabolism and pyroptosis-related markers and histological analysis (Hematoxylin & Eosin and Masson staining) was employed to examine alterations in endometrial morphology. Finally, a fertility test was performed to evaluate the restoration of the uterine function. Results: Following endometrial injury, the expression of key endogenous H2S enzymes-cystathionine β-synthase (CBS), cystathionine γ-lyase (CSE), and 3-mercaptopyruvate sulfurtransferase (MST)-is significantly reduced, while the levels of pyroptosis-related proteins are elevated (p < 0.05). However, treatment with H2S resulted in an increase in the expression of endogenous H2S enzymes and a decrease in pyroptosis-associated proteins compared to the Model group (p < 0.05). Moreover, endometrial morphology and embryo count showed the most pronounced improvement in the H2S treatment group (p < 0.05). Conclusions: This study confirms the therapeutic efficacy of H2S in facilitating the recovery of injured endometrium and revealed its potential therapeutic mechanism, offering a promising therapeutic avenue for patients with severe endometrial injury.